2020
DOI: 10.1089/end.2020.0402
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Acute Pain Management for Renal Colic in the Emergency Department at a Tertiary Care Academic Medical Center

Abstract: Introduction: Renal colic secondary to kidney stone disease is a common reason for emergency department (ED) visits and often leads to patients receiving narcotic medications. The objective of this study was to describe longitudinal analgesia prescribing patterns for kidney stone patients acutely managed in the ED. Methods: This was a retrospective chart review of patients who presented to the ED between 2013 and 2018 and were subsequently diagnosed with a kidney stone. Encounters during which opioids and nono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
3
3
0
3
Order By: Relevance
“…The difference in the proportion of patients receiving an opioid analgesic prescription between this study and that in Cotta et al 12 could be due to several factors: variation in prescribing between hospitals (within hospitals in this study 52-95% of visits received an opioid analgesic prescription); our sample of ED visits (Cotta et al noted that patients with an initial visit to the ED were more likely to receive a prescription than if the initial visit was at an urgent care or another clinic type) 12 ; and finally, a possible decrease in prescribing over time, although this change has been found to be minimal for urolithiasis compared to other contexts. [17][18][19] Consistent with our results, the retrospective study found that those who received an opioid analgesic prescription at their initial visit were more likely to require a refill during the acute stone episode than those who did not receive an opioid prescription at the initial visit.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The difference in the proportion of patients receiving an opioid analgesic prescription between this study and that in Cotta et al 12 could be due to several factors: variation in prescribing between hospitals (within hospitals in this study 52-95% of visits received an opioid analgesic prescription); our sample of ED visits (Cotta et al noted that patients with an initial visit to the ED were more likely to receive a prescription than if the initial visit was at an urgent care or another clinic type) 12 ; and finally, a possible decrease in prescribing over time, although this change has been found to be minimal for urolithiasis compared to other contexts. [17][18][19] Consistent with our results, the retrospective study found that those who received an opioid analgesic prescription at their initial visit were more likely to require a refill during the acute stone episode than those who did not receive an opioid prescription at the initial visit.…”
Section: Discussionsupporting
confidence: 83%
“…17 For the years 2013-2018, other individual EDs reported decreases from 70% to 52% 19 and from 81% to 59%. 18 Had the present investigation been repeated in 2018, we would expect to see fewer than 79.6% of urolithiasis patients receive an opioid analgesic prescription at ED discharge, likely close to the 59% observed in the Kominsky et al study. 18 However, we do not have reason to expect the relationship between opioid analgesic prescribing and use to change over time.…”
Section: Limitationssupporting
confidence: 65%
See 3 more Smart Citations